32. EVALUATION OF CASES OF TREATING OVARIAN CYST RUPTURED BY LAPAROSCOPIC AT THANH NHAN HOSPITAL FROM 2018 TO 2023 (Tạp chí Y học Cộng đồng, 2024)
Objective: Evaluate treating ovarian cyst ruptured by laparoscopic.Subject and methods: 26 patients who underwent laparoscopic surgery to treat ruptured ovarian cyst at Thanh Nhan hospital from January 2019 to June 2023.Results: The disease was common in the age group 500 ml of blood in the abdomen, and Three of them had > 1000 ml. 100% of patients underwent ovary-conserving surgery. 92,3% had early surgery which was performed under 24 hours. 100% no complications in surgery.Conclusion: Ovarian cyst rupture can cause hemorrhagic shock and should be diagnosed and treated early. The main treatment method is laparoscopic surgery to preserve the ovaries.
Keywords: Rupture of functional cyst; surgery